The role of the freshwater shrimp atyaephyra desmarestii in leaf litter breakdown in streams - Duarte, Sofia Alexandra Ferreira (2012)
This version does not correspond to the published one. To access the final version go to: http://www.springerlink.com/content/a31518u452m03286/